2009
DOI: 10.1103/physrevb.79.054408
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and Bell’s inequality violation above room temperature in metal carboxylates

Abstract: In the present work we show that a special family of materials, the metal carboxylates, may have entangled states up to very high temperatures. From magnetic susceptibility measurements, we have estimated the critical temperature below which entanglement exists in the cooper carboxylate {Cu2(O2CH)4}{Cu(O2CH)2(2-methylpyridine)2}, and we have found this to be above room temperature (Te ∼ 630 K). Furthermore, the results show that the system remains maximally entangled until close to ∼ 100 K and the Bell's inequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 36 publications
1
55
0
1
Order By: Relevance
“…Algoritmos baseados nas propriedades do Mn12Ac já foram propostos, assim como a existência de estados quanticamente emaranhados. 101 Um grande esforço tem sido feito no desenvolvimento da tecnologia de manipulação de spins, como a técnica de ressonância paramagnética eletrônica pulsada, para aplicação futura em dispositivos para computação quântica. 4 …”
Section: Perspectivas De Aplicação De Smmunclassified
“…Algoritmos baseados nas propriedades do Mn12Ac já foram propostos, assim como a existência de estados quanticamente emaranhados. 101 Um grande esforço tem sido feito no desenvolvimento da tecnologia de manipulação de spins, como a técnica de ressonância paramagnética eletrônica pulsada, para aplicação futura em dispositivos para computação quântica. 4 …”
Section: Perspectivas De Aplicação De Smmunclassified
“…In spite of that, it is fragile and can easily vanish due to the inevitable interaction of the system with its environment [4]; and due to this condition, it was thought that entanglement could only exist at low temperatures. However, recently, it has been shown that entanglement can also exist at higher temperatures, and can be detected through the measurement of some thermodynamic observables [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Abstract: Quantum Discord Geometric Correlations Molecularmentioning
confidence: 99%
“…They combine classical properties, found in any macroscopic magnet, with quantum ones, such as quantum interference and entanglement. The large gap between the ground state and the first-excited state found in some materials allows the existence of entangled quantum states at higher temperatures [6,11,13,17]. The study of molecular magnets opens thus doors for new research toward to the limits of quantum mechanics; and several aspects are worthy of a thorough research, such as (i) how robust their quantum features are against temperature and (ii) how large systems can support these properties.…”
mentioning
confidence: 99%
See 2 more Smart Citations